Psychometric properties of HITS-Brazil: Instrument for screening domestic violence against the elderly (Research, Society and Development, 2020)
This study aims to evaluate the psychometric properties (validity and reliability) of the Hurt Insult Threatened Scream (HITS) instrument for the screening of domestic violence against the elderly. Participated in this sample 48 elderly people and descriptive and inferential statistics were used to analyze the results. Reliability was tested by measuring intra-observer agreement and internal consistency. Intra-observer agreement was verified in the HITS Brazil itens and in the total score by the Intraclass Correlation Coefficient (ICC), with the following classification: ICC